Is globalization the root cause of declining inflation? - Juhana Hukkinen; Matti E. E. Virén (Aboa Centre for Economics (ACE), 2022)
This paper examines the reasons for the declining path of inflation since the 1970s. In particular, it focusses on the role of globalization - covering both changes in the global market structure and technical and structural developments in trade and production. In addition, the paper deals with changes in the basic transmission mechanisms of price and wage inflation. The paper makes use of different data from individual countries and panel of countries. These data show that the dispersion of inflation and the behavior of relative prices follow a pattern that is consistent with several globalization indicators. Also estimation results show that these indicators are useful in tracing the developments of trend inflation after the 1960s. Moreover, it is shown that the basic relationships between prices and costs are nonlinear depending on the level of inflation.
Keywords: E31; E52; E58; F02; F41; F42; F62; 330; Inflation; globalization; Phillips curve; trade unions